Revitalization of Islamic Psychotherapy: The Incorporation of Spiritual Values in Rehabilitation Center - Farid A., Ikram; Aminah, Soraya (Indonesian Journal of Islamic Counseling, 2025)
This article explores the role of Islamic psychotherapy in the rehabilitation of students (santri) at the Salafiyah Syafi’iyah Nashrun Minallah Islamic Boarding School, focusing on the incorporation of spiritual values. This research uses a qualitative method with a case study design to analyze the impact of incorporating spiritual values in therapy. The research findings show that the integration of spiritual values in Islamic psychotherapy significantly enhances the emotional and spiritual conditions of the students. Key findings include increased inner peace, positive behavioral changes, improved self-motivation, and better social relationships and quality interactions. Additionally, the students demonstrated increased resilience, better abilities to face life challenges, and a deeper understanding of the meaning of life. This research also emphasizes that this approach not only serves as a method of individual healing but also strengthens the overall community of the boarding school. These conclusions affirm the importance of integrating spiritual values in rehabilitation programs to achieve better psychological and social well-being.